Pemantauan Tumbuh Kembang Bayi dan Balita dan Edukasi Gizi dalam Pencegahan Stunting di Posyandu Anggrek di Kelurahan Banyurip Kota Pekalongan - Maslikhah Maslikhah; Hilda Prajayanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Stunting is a condition of growth failure in children under five due to chronic malnutrition, especially in the first 1,000 days of life (HPK). Stunting affects brain growth and development so that there is a higher risk of suffering from chronic diseases in adulthood. The effort to handle stunting is by maximizing Posyandu. Posyandu can function as a comprehensive early detection, handling and consultation on stunting.) Posyandu cadres must be able to take part in efforts to deal with stunting, at least by being able to carry out early detection of stunting, the existence of posyandu can help monitor the development of nutritional status of toddlers based on recording and reporting taken from data on the results of weighing toddlers. The method used in this community service activity is through counseling activities for parents in the Anggrek Posyandu area, Banyurip Village, Pekalongan City. The results of this activity increased the knowledge of participants, namely good knowledge as much as 92% from the previous counseling only 34%.